RERATA VOLUME TROMBOSIT, HITUNG LEUKOSIT DAN TROMBOSIT DI APENDISITIS AKUT - Jayadi Festiawan; Nurhayana Sennang; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
The diagnosis of acute appendicitis and its complications still depends on the radiological examination and laparoscopy techniques.The aim of this study was to know the Mean Platelet Volume (MPV), WBC and platelet value in the diagnosis of acute appendicitis,associated with the incidence of existing complications. This research was carried out by a retrospective study by taking secondary datafrom the medical records, including the results of routine blood tests of acute appendicitis patients with and without complications atthe Dr. Wahidin Sudirohusodo Hospital between May 2011− May 2012. The data obtained in the study were MPV, White Blood Cell(WBC) and platelet count which were then analyzed using independent T test. The results obtained from 44 samples were that MPVvalues showed a significant difference (p=0.02), while WBC (p=0.12) and platelet count (p=0.13) were statistically not significantlydifferent between patients with and without complications. In conclusion, it was found that acute appendicitis with complications hadhigher MPV average values than those without complications and although there were significant differences between them, these werestill within the normal values.